The neuroprotective and antidepressant‐like effects of Hcyb1, a novel selective PDE2 inhibitor. (27th April 2018) - Liu, Li; Zheng, Jing; Huang, Xian‐Feng; Zhu, Xia; Ding, Shu‐Ming; Ke, Heng‐Ming; O'Donnell, James M.; Zhang, Han‐Ting; Song, Guo‐Qiang; Xu, Ying
Summary: Aims: Depression is currently the most common mood disorder. Regulation of intracellular cyclic adenosine monophosphate (cAMP) and/or cyclic guanosine monophosphate (cGMP) signaling by phosphodiesterase (PDE) inhibition has been paid much attention for treatment of depression. This study aimed to investigate the neuroprotective effects of Hcyb1, a novel PDE2 inhibitor, in HT‐22 cells and antidepressant‐like effects in mouse models of depression. Methods: Hcyb1 was synthesized and its selectivity upon PDE2 was tested. Moreover, HT‐22 hippocampal cells were used to determine the effects of Hcyb1 on cell viability, cyclic nucleotide levels, and the downstream molecules related to cAMP/cGMP signaling by neurochemical, enzyme‐linked immunosorbent, and immunoblot assays in vitro. The antidepressant‐like effects of Hcyb1 were also determined in the forced swimming and tail suspension tests in mice. Results: Hcyb1 had a highly selective inhibition of PDE2A (IC50 = 0.57 ± 0.03 μmol/L) and over 250‐fold selectivity against other recombinant PDE family members. Hcyb1 at concentrations of 10 −10 and 10 −9 mol/L significantly increased cell viability after treatment for 24 hours. At concentrations of 10 −9 10 −7 mol/L, Hcyb1 also increased cGMP levels by 1.7 2.3 folds after 10‐minute treatment. Furthermore, Hcyb1 at the concentrations of 10 −9 mol/L increased both cGMP and cAMP levels 24 hours after treatment. The levels of phosphorylation of CREB and BDNF were also increased by Hcyb1 treatment in HT‐22 cells for 24 hours. Finally, in the in vivo tests, Hcyb1 (0.5, 1, and 2 mg/kg, i.g.) decreased the immobility time in both forced swimming and tail suspension tests, without altering locomotor activity. Conclusion: These results suggest that the novel PDE2 inhibitor Hcyb1 produced neuroprotective and antidepressant‐like effects most likely mediated by cAMP/cGMP‐CREB‐BDNF signaling.